2020
DOI: 10.31219/osf.io/58wzp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical Significance Testing at CHI PLAY: Challenges and Opportunities for More Transparency

Abstract: Statistical Significance Testing -- or Null Hypothesis Significance Testing (NHST) -- is common to quantitative CHI PLAY research. Drawing from recent work in HCI and psychology promoting transparent statistics and the reduction of questionable research practices, we systematically review the reporting quality of 119 CHI PLAY papers using NHST (data and analysis plan at https://osf.io/4mcbn/. We find that over half of these papers employ NHST without specific statistical hypotheses or research questions, which… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Thus, Hornbaek et al [25] found that only 3% of HCI articles across 4 outlets in 2014 were replications, and many of these accidental. Vornhagen and colleagues [53] investigated current practices involving transparency and null hypothesis significance testing in papers at the CHI sister conference CHI PLAY. Only 20% of the studied CHI PLAY papers included detailed materials (questionnaires, software, etc), less than 5% were accompanied by open data, and none of them shared their analysis code.…”
Section: Open Science and Hcimentioning
confidence: 99%
“…Thus, Hornbaek et al [25] found that only 3% of HCI articles across 4 outlets in 2014 were replications, and many of these accidental. Vornhagen and colleagues [53] investigated current practices involving transparency and null hypothesis significance testing in papers at the CHI sister conference CHI PLAY. Only 20% of the studied CHI PLAY papers included detailed materials (questionnaires, software, etc), less than 5% were accompanied by open data, and none of them shared their analysis code.…”
Section: Open Science and Hcimentioning
confidence: 99%